2020
DOI: 10.3390/nu12113286
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Vitamin C in the Prevention and Treatment of COVID-19

Abstract: Investigation into the role of vitamin C in the prevention and treatment of pneumonia and sepsis has been underway for many decades. This research has laid a strong foundation for translation of these findings into patients with severe coronavirus disease (COVID-19). Research has indicated that patients with pneumonia and sepsis have low vitamin C status and elevated oxidative stress. Administration of vitamin C to patients with pneumonia can decrease the severity and duration of the disease. Critically ill pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 44 publications
2
127
0
1
Order By: Relevance
“…The inflammatory response has led researchers to believe that there might be possible differences in the redox profile of patients with COVID-19 [ 8 , 15 , 16 ], and thus, the use of antioxidants as a complementary therapeutic strategy in COVID-19 has been proposed [ [37] , [38] , [39] , [40] ]. Oxidative stress affects the immune system through altering the immune cell function and inflammatory response [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response has led researchers to believe that there might be possible differences in the redox profile of patients with COVID-19 [ 8 , 15 , 16 ], and thus, the use of antioxidants as a complementary therapeutic strategy in COVID-19 has been proposed [ [37] , [38] , [39] , [40] ]. Oxidative stress affects the immune system through altering the immune cell function and inflammatory response [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the excellent safety profile of vitamin C and the necessity of ICU treatment for a high proportion of COVID-19 patients may justify consideration of clinical application of vitamin C, even before the results of large clinical trials are available ( 24 ). Vitamin C has been proposed for COVID patients also by other authors ( 25 27 ).…”
Section: Discussionmentioning
confidence: 90%
“…According to the authors, a significant decrease in intensive care unit stay and hospital mortality was observed in the vitamin C treated patients [ 44 ]. Overall, vitamin C seemed to possess relevant pharmacological properties against severe respiratory infections, including COVID-19 [ 45 , 46 ]. Several clinical trials, assessing the efficacy of high dose vitamin C infusion, are still ongoing and will provide more definitive evidence.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, vitamin C seemed to possess relevant pharmacological properties against severe respiratory infections, including COVID-19 [45,46]. Several clinical trials, assessing the efficacy of high dose vitamin C infusion, are still ongoing and will provide more definitive evidence.…”
Section: Vitamin Cmentioning
confidence: 99%